End game [large type] - Baldacci, David (Baldacci, David. Will Robie series., 2017)
Will Robie and Jessica Reel are two of the most lethal people alive. They're the ones the government calls in when the utmost secrecy is required to take out those who plot violence and mass destruction against the United States. And through every mission, one man has always had their backs: their handler, code-named Blue Man. But now, Blue Man is missing. Last seen in rural Colorado, Blue Man had taken a rare vacation to go fly fishing in his hometown when he disappeared off the grid. With no communications since, the team can't help but fear the worst. Sent to investigate, Robie and Reel arrive in the small town of Grand to discover that it has its own share of problems. A stagnant local economy and a woefully understaffed police force have made this small community a magnet for crime, drugs, and a growing number of militant fringe groups.